Usutu Virus Antibody Dynamics in Naturally Infected Blackbirds, the Netherlands, 2016–2018 - Erwin de Bruin; Jurrian van Irsel; Felicity Chandler; Robert Kohl; Tess van de Voorde; Anne van der Linden; Fred de Boer; Marion Koopmans; Henk van der Jeugd; Chantal Reusken (Emerging Infectious Diseases)
Usutu virus is a zoonotic arbovirus that causes massive mortality in blackbirds. Using a unique longitudinal dataset on the kinetics of virus-specific antibodies in naturally infected wild blackbirds (Turdus merula), we found that individual birds may remain seropositive for >1 year and that reinfection can occur despite low-level virus neutralizing antibodies.